Perbaikan Pertumbuhan dan Kualitas Tanaman Lidah Buaya di Tanah Gambut dengan Aplikasi Mikoriza Arbuskula dan Pemupukan - Iwan Sasli; Sudirman Yahya; , Sudradjat; Yadi Setiadi; , Sudarsono (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2008)
This research was aimed at studying the effectiveness of mycorrhiza, inorganic and organic fertilizer (fish and shrimp waste) on growth, yield and quality of Aloe in peat soil. The study was conducted on peat area, North Pontianak, West Kalimantan. Mycorrhizal application levels (without mycorrhiza, Mycofer and mycorrhizal from pineapple's rhizosphere) were as main-plot. The inorganic fertilizer (composition of N:P:K:Mg) rates (without inorganic fertilizer; 5 : 4 : 7.5 : 2.5 g/plant; 10 : 8 : 15 : 5 g/plant; and 20 : 16 : 30 : 10 g/plant) were as sub-plot. Organic fertilizers: (fish; shrimp; fermented fish; and fermented shrimp wastes) were as sub-sub plot. The observed variables were: leaf width, leaf length, leaf fresh weight, plant dry weight, and nutrient uptake (N, P, K, Mg). The results showed that mycorrhizal application improved growth performance and increased N, P, Mg uptake. The best plant growth performance was achieved by N : P: K : Mg =10 : 8 : 15 : 5 g/plant and fermented shrimp waste treatments. The highest N, P, K, Mg nutrients uptake was achieved by application of fermented organic fertilizer. Combination of mycorrhiza from pineapple's rhizosphere with fermented fish and shrimp waste resulted in higher amino acids content compared to standard cultivation of Aloe vera Center in Pontianak. Key words: Aloe vera, arbuscular mycorrhiza, inorganic fertilizer, organic fertilizer